THE EFFECT OF WORD BOX GAME ON THE EIGHTH GRADE STUDENTS’ VOCABULARY MASTERY - Hesti Wulandari; Arjulayana Arjulayana; Sumiyani Sumiyani (Universitas Muhammadiyah Tangerang, 2019)
Vocabulary is first thing to do and one micro skill that must be raise to help the students mastering four language skills. If the students have a lack of vocabulary, they will find some difficulties in expressing ideas in oral or written. In addition, if the students have less vocabulary, they also cannot access the information or knowledge. Moreover, without the words the students cannot really understand facts or ideas that the students have met. Therefore, the students should have to obtain vocabulary mastery to communicate effectively or express his ideas in both oral and written form and also used as basic foundation to construct a word into a good sequence of sentence. Due to the statement, this study is aimed to find out the effect of word box game on the eighth grade students’ vocabulary mastery at Mts Mathla’ul Anwar. The research method is using quasi experimental design and analyze the data by using statitistical hypothesis. Based on the data analysis, it was found that the data was normally distributed and homogeneous. Then, the researchers used t-test formula to analyze the hypotheses. From hypothesis test using t-test, obtained tcount was smaller than ttable or 1.54 < 1.67 on pre-test and on post-test that tcount was higher than ttable or 8.92 > 1.67 with the degree of significant α = 0.05 and df = 35 + 35 - 2 = 68. Thus, it can be concluded that there is difference of students’ vocabulary mastery between using word box game and without word box game in experiment and control class.